2022
DOI: 10.1038/s41420-022-00975-w
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of lncRNA MALAT1 facilitates erastin-induced ferroptosis in endometriosis through miR-145-5p/MUC1 signaling

Abstract: Endometriosis is a chronic disorder characterized by the implantation of endometrial glands and stroma outside the uterus. However, the pathogenesis of endometriosis is still unclear. To date, there is no fully effective treatment without trauma because of various side effects. Recent data suggest that ferroptosis is a novel recognized form of nonapoptosis-regulated cell death characterized by iron-dependent and lethal lipid peroxidation accumulation, showing great promise in the treatment of many diseases. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…The diagnosis of endometriosis was established through laparoscopy and histological confirmation. As controls, endometrial tissue samples were obtained from cycling women, age-and menstrual phase-matched (in frequency) with those endometrioses who underwent hysterectomy with uterine leiomyoma or grade II-III cervical intraepithelial neoplasia (CIN), and without clinical indication or history of endometriosis or adenomyosis [32,33]. The tissue sampled in our study was approved by the Human Assurance Committee of Affiliated Hospital of Weifang Medical University (Ethics number 2021YX028).…”
Section: Tissue Samples and Endometriosis Mouse Modelmentioning
confidence: 99%
“…The diagnosis of endometriosis was established through laparoscopy and histological confirmation. As controls, endometrial tissue samples were obtained from cycling women, age-and menstrual phase-matched (in frequency) with those endometrioses who underwent hysterectomy with uterine leiomyoma or grade II-III cervical intraepithelial neoplasia (CIN), and without clinical indication or history of endometriosis or adenomyosis [32,33]. The tissue sampled in our study was approved by the Human Assurance Committee of Affiliated Hospital of Weifang Medical University (Ethics number 2021YX028).…”
Section: Tissue Samples and Endometriosis Mouse Modelmentioning
confidence: 99%
“…We found MALAT1 was positively associated with exosome characteristics, and others found that exosome-mediated intercellular communication allowed the transfer of MALAT1 as a lncRNA to play a regulatory role ( 54 , 55 ). In contrast, MALAT1 was negatively associated with ferroptosis signature, and one study reported that silencing MALAT1 induced ferroptosis ( 56 ), reflecting the possibility that MALAT1 may also contribute to the development of HCC by inhibiting ferroptosis. TIL prediction analysis showed that high MALAT1 expression was associated with several immunosuppressive signatures, such as reduced macrophage infiltration and increased fibroblast infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…To systemically explore the potential ceRNA mechanisms between these differentially expressed lncRNAs and Becn1, miRNAs bound with Becn1 and lncRNAs bound with miRNAs were predicted respectively by Starbase database, then the predicted lncRNAs were intersected with the differentially up-regulated lncRNAs to obtain lncRNA/miRNA/mRNA ceRNA network, the results showed there were Rian/mmu-miR-145a-5p/Becn1, Tug1/mmu-miR-145a-5p/Becn1, Malat1/mmu-miR-30e-5p/Becn1 and H19/mmu-miR-299a-3p/Becn1 axes respectively. There have been reported that lncRNA Rian, lncRNA Tug1, lncRNA Malat1 and lncRNA H19 all serve as ceRNA involved in multiple biological process, such as apoptosis ( Wu et al, 2020 ; Yao et al, 2020 ), ferroptosis ( Liang et al, 2022 ; Zhang et al, 2022 ) and pyroptosis ( Sun, Mao & Ji, 2021 ; Kang et al, 2022 ). Zhang and He reported that lncRNA Malat1/mmu-miR-30a/Becn1 was involved in myocardial infarction ( Zhang & He, 2020 ).…”
Section: Discussionmentioning
confidence: 99%